Validity of the Content of Science E-Module Based on Problem Based Learning Containing Ethnoscience to Improve Students' Critical Thinking Ability - Ula, Azizatul; Setyono, Prabang; Yamtinah*, Sri; Havyarimana, Clestin (Universitas Syiah Kuala, 2025)
Biodiversity ecology and ethnoscience are materials that are considered difficult to understand because they have to relate abstract material to the problems of everyday life and also the culture/beliefs of a region. Interactive teaching materials play a role in increasing students understanding and improving their critical thinking abilities. This research aims to produce interactive teaching materials based on electronic modules that are valid to use as learning media. This research employs a descriptive qualitative approach for data analysis. The content validity in this research includes media validity, material validity, learning expert validity and language validation which have been validated by expert validators and practitioners according to their fields. Aspects measured for media validation include learning unit presentation techniques, presentation completeness, e-module size, cover design, and learning unit content design, while material validity includes aspects of material completeness, material breadth, material depth, material accuracy, and up-to-date and contextual. Learning expert validation includes content, strategies, learning evaluation and assessment. Linguist validation includes straightforward, communicative, dialogical, and interactive, suitability for student development, language and slides or icons. Based on the research results, the average validity test for material was 0.89, media was 0.90, learning expert was 0.94 and language was 1.00, these four validations can be stated to be included in the valid category. It was concluded that the science e-module is suitable for use as a learning medium based on Problem Based Learning and containing ethnoscience to improve students' critical thinking skills on ecology and biodiversity material